OFFICIAL DEVELOPMENT ASSISTANCE EFFECT ON ROAD SAFETY AND ROAD FATALITIES: AN EMPIRICAL ANALYSIS FOR SELECTED DEVELOPING COUNTRY SAMPLES (Third Sector Social Economic Review, 2020)
More than 1.3 million people die every year in road accidents. Eighty percent of deaths due to road accidents are seen in underdeveloped or developing countries. Injuries, deaths and material losses due to road accidents place heavy burdens on health systems and budgets of underdeveloped countries. The aim of this study is to examine the effects of official development assistance on mortal road accidents on a sector by sector basis and to make recommendations in the field of the effectiveness of aid. In the study, the relationship between the number of deaths in per 1 million population in road accidents between 2005-2016 in Vietnam, Serbia, Bosnia and Herzegovina, Armenia and Georgia and the development aids received by countries in the field of transportation and health were analyzed using regression analysis method. In addition, the relationship between development assistance and the variable of income per capita which is expected to affect indirectly was also examined statistically. The findings of the study indicate that there is a statistically significant relationship between the development assistance on road transportation and the deaths in per 1 million population, in Vietnam, Bosnia and Herzegovina and Serbia. Accordingly, it is recommended to prioritize development assistance on a sector and need basis, to provide institutional and legal infrastructure in order to collect correct data from the field, and to develop institutional and legal capacity when the country's infrastructure and institutional capacities are not sufficient.
Keywords: Development Assistance; Road safety; Underdeveloped and Developing Countries; Road Fatalities